Clinical evaluation of a new dental unit designed to prevent internal contamination - Ohsuka, Shinji; Ohta, Michio; Ashoori, Mandana; Usami, Takeshi; Ito, Masao; Masuda, Koji; Ueda, Minoru (Journal of Japanese Society of Dentistry for Medically Compromised Patient, 1994)
This experiment was performed under clinical condition of a dental office to examine the suck-back occurrence, and also to report the efficacy of the AT/AR Clean System against suck-back in vivo. A new autoclavable device AT/AR Clean System (Morita Co., Ltd., Kyoto, Japan) was made to reduce cross-contamination by suck-back inside the air-turbine handpiece when it is stopped. For this study, the handpieces with or without anti-suck-back device were disinfected with 2% neutral glutalaldehyde and replaced with sterilized handpieces in an autoclave. The samples were taken before and after dental treatment and after replacing a sterilized handpiece. Culture was performed for 72 hours aerobically to detect the residual microorganisms inside the handpiece. The results proved extreme efficacy to reduce bacterial contamination in compare with the conventional type of handpieces. Furthermore suck-back may occur under present clinical condition of the dental clinics, but even without usage of anti-suck-back device the operator's skill and an appropriate management could reduce cross-contamination markably.